Pattern of Admission and Outcome in a Neonatal Intensive Care Unit (NICU) of a Tertiary Care Hospital in Dhaka, Bangladesh - Tajkia, Gule; Amin, Syed Khairul; Rahman, M Ekhlasur; Setu, Mumtahina; Roy, Kuntal; Halder, Soma; Rahman, Mohammad Mahbubur (Anwer Khan Modern Medical College Journal, 2019)
Background: The neonatal period is a highly vulnerable time for an infant completing many of the physiologic adjustments required for life outside the uterus. As a result, there are high rates of morbidity and mortality. To reduce morbidity and mortality it is essential to know the neonatal disease pattern. Neonatal disease pattern changes from time to time and place. Analyzing the neonatal admission pattern helps the policy makers to make the better strategies and health care givers to serve better. Objectives: This study aimed to determine the disease patterns and outcome of patients admitted to the Neonatal Intensive Care Unit (NICU) of Anwer khan Modern Medical College Hospital, a tertiary care hospital in Dhaka, between January 2017 to December 2018. Methods: Retrospective data from the medical records of all neonates admitted during the study period were reviewed and analyzed for age, weight, sex, reason for admission, duration of hospital stay, diagnosis and final outcome. Results: The total number of neonates admitted during the study period was 262; 164 were male (62.6%), and 98 were female (37.4%). A total of 223 patients (85.12%) wereborn in the hospital while 39 (12.88%) were born at home. The majority were admitted during the first 48 hours of life (72.2%). A total of 5 patients (2%) weighed <1000 gm; 53(20.2%) weighed 1000-1500 gm, and 89 (34%) between 1600-2499 gm. Prematurity and infection were the main reasons for admission (52.7% and 20%, respectively), followed by birth asphyxia (12%) and neonatal jaundice (6.8%). A total of 206 patients (78.6%) were improved and discharged, 43 left against medical advice (16.4%), 3 were referred for urgent cardiac intervention (1.1%) and 10 (3.9%) died. Conclusion: Prematurity, neonatal infection and birth asphyxia were the major causes of neonatal morbidity and mortality. Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 150-158